2008
DOI: 10.1161/circulationaha.107.742692
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Myocardial Infarction in Mice Lacking All Nitric Oxide Synthase Isoforms

Abstract: Background-The roles of nitric oxide (NO) in the cardiovascular system have been investigated extensively in pharmacological studies with NO synthase (NOS) inhibitors and in studies with NOS isoform-deficient mice. However, because of the nonspecificity of the NOS inhibitors and the compensatory interactions among NOS isoforms (nNOS, iNOS, and eNOS), the ultimate roles of endogenous NO derived from the entire NOS system are still poorly understood. In this study, we examined this point in mice deficient in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 49 publications
9
106
1
3
Order By: Relevance
“…It has been reported that SREBP-2 activity and LDL receptor expression were decreased in HFD-fed n/i/eNOSs −/− mice associated with severe dyslipidemia (Yatera et al 2010). Although it has been reported that serum lipids levels are increased in ND-fed n/i/eNOSs −/− mice (Nakata et al 2008), we showed that SREBP-2 activity and LDL receptor expression were decreased even in ND-fed n/i/eNOSs −/− mice in the present study.…”
Section: Mouse Models Of Metabolic Disordersmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been reported that SREBP-2 activity and LDL receptor expression were decreased in HFD-fed n/i/eNOSs −/− mice associated with severe dyslipidemia (Yatera et al 2010). Although it has been reported that serum lipids levels are increased in ND-fed n/i/eNOSs −/− mice (Nakata et al 2008), we showed that SREBP-2 activity and LDL receptor expression were decreased even in ND-fed n/i/eNOSs −/− mice in the present study.…”
Section: Mouse Models Of Metabolic Disordersmentioning
confidence: 98%
“…In the present study, we used HFD-fed WT mice as a model of metabolic disorder. On the other hands, we fed NOSs −/− (eNOS −/− , n/eNOSs −/− and n/i/ eNOSs −/− ) mice with ND since these mice are known as animal models of metabolic disorders (Nakata et al 2008). In the skeletal muscle, the long-term treatment with fasudil significantly increased ACC activity but not AMPK activity in both HFD-fed WT mice and n/i/eNOSs −/− mice.…”
Section: Mouse Models Of Metabolic Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…The n/i/eNOS / mice are unexpectedly viable and appear normal, but their survival and fertility rates are markedly reduced as compared with wild-type (WT) mice. The n/i/ eNOS / mice spontaneously develop cardiovascular diseases, including hypertension, dyslipidemia, and arteriosclerosis [56,57]. It, however, remains to be determined whether or not the NOS system plays a role in maintaining cardiac architecture and function.…”
Section: Role Of the Entire Nos System In Heart Failurementioning
confidence: 99%